1987
DOI: 10.1111/j.1095-8649.1987.tb05315.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic examination of antigen uptake by salmonid gill cells after bath immunization with a bacterin

Abstract: Atlantic salmon, Salmo salar, were given 2-min bath immunization with Yersinia ruckeri 0-antigen bacterins at doses of 10, 100, and lo00 c(g mi-l . The uptake of the antigen was followed by light and electron microscopy of samples taken immediately and periodically after immunization, and the immune response monitored by the passive haemolytic plaque assay. The particulate antigen was observed in the gill mucus, adhering to and within the pavement cellscoveringthe gill filaments, and in mononuclear phagocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 20 publications
2
26
1
Order By: Relevance
“…Amend & Fender (1976), observing the time course of BSA concentration in various organs after bath treatment, stated that the main site responsible for uptake of antigen is the lateral line. In contrast, later studies reported that the gill is the main site of antigen uptake (Bower & Alexander, 1981;Alexander et al, 1981), and this is generally accepted at present (Smith, 1982;Tatner et al, 1984;Zapata et al, 1987;Kawahara & Kusuda, 1988). The intestine has also been proposed as a site of antigen uptake (Robohm, 1986;Rombout et al, 1985;Tatner, 1987;Robohm & Koch, 1995).…”
Section: Introductionmentioning
confidence: 76%
“…Amend & Fender (1976), observing the time course of BSA concentration in various organs after bath treatment, stated that the main site responsible for uptake of antigen is the lateral line. In contrast, later studies reported that the gill is the main site of antigen uptake (Bower & Alexander, 1981;Alexander et al, 1981), and this is generally accepted at present (Smith, 1982;Tatner et al, 1984;Zapata et al, 1987;Kawahara & Kusuda, 1988). The intestine has also been proposed as a site of antigen uptake (Robohm, 1986;Rombout et al, 1985;Tatner, 1987;Robohm & Koch, 1995).…”
Section: Introductionmentioning
confidence: 76%
“…Torroba et al (1993) showed that formalin-killed Y. ruckeri were taken up by gill epithelial cells during an in vitro assay where isolated rainbow trout gills were placed in medium containing the killed bacteria. Zapata et al (1987) demonstrated that killed Y. ruckeri bacteria were taken up by the gill cells of Atlantic salmon after bath immunization. However, results obtained with dead bacteria may differ from these with viable bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The process of suspended particle uptake by the gills was well studied by Zapata et al (1987) and Goldes et al (1986). Zapata et al (1987) examined the uptake by Atlantic salmon of the Yersinia ruckeri particulate antigen by electron microscopy after brief immersion in antigen suspension. Antigens were found in the gill mucus, adhering to and within pavement cells, and in mononuclear phagocytes lying directly beneath these cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fishes, there seems no doubt that environmental particles, including particulate antigens, are taken into the body surface tissue (Goldes et al, 1986;Zapata et al, 1987;Moore et al, 1998). Moore et al (1998) indi cated that the skin, rather than gills, plays a major role in the uptake of particulate antigens, and that the antigens are internalized primarily within epithelial cells and underlying phagocytes.…”
mentioning
confidence: 99%